IMPROVING STUDENTS’ SPEAKING SKILL BY IMPLEMENTATION OF FOLKLORE MONOLOGUE PERFORMANCE AT THE TENTH GRADE OF SMA COKROAMINOTO MAKASSAR - Nur Afifi, Zebkiah; Kaddas, Badruddin; N, Jusmaniar (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2025)
This study aimed to improve the speaking skills of tenth-grade students at SMA Cokroaminoto Makassar by using monologue performances of South Sulawesi folklore. This research used classroom action research, in which data were obtained from speaking tests. The subject of the study consisted of 20 tenth-grade students from SMA Cokroaminoto Makassar. The results showed that students' speaking skills before and after using the monologue performances differed significantly. The average score from the students' test was 64.45, while the average score on the final test in cycle 1 increased to 70.5. However, it had not yet reached the English subject standard score (78). Then, the average score from the final test in cycle 2 was 80.1, indicating an improvement of 13.6% from cycle 1 to cycle 2. In addition, the frequency of students’ scores, specifically in speaking fluency in cycle 1 showed that 14 students (70%) received good scores, while 6 students (30%) received fair scores. In cycle 2, there was an improvement, with 14 students (70%) achieving very good scores and 6 students (30%) receiving good scores. This indicated that there was a significant improvement in students’ speaking skills after using monologue performances of South Sulawesi folklore. Based on the results of the study, it could be concluded that the implementation of South Sulawesi folklore monologue performances was effective in improving the speaking skills of tenth-grade students at SMA Cokroaminoto Makassar.